A facile synthesis of mesoporous Co3O4/CeO2 hybrid nanowire arrays for high performance supercapacitors1. Issue 19 (21st May 2015) - Cui, Jiewu; Zhang, Xinyi; Tong, Liang; Luo, Jinbao; Wang, Yan; Zhang, Yong; Xie, Kui; Wu, Yucheng
<x xml:space="preserve">Abstract</x> Mesoporous Co3O4/CeO2 hybrid nanowire arrays are synthesized and employed as electrode materials for supercapacitors. These nanomaterials exhibit remarkable pseudocapacitance and superior cycling stability.